2011
DOI: 10.1108/09684881111158063
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management in Malaysian school education

Abstract: PurposeThe purpose of this paper is to shed light on changes in the Malaysian education system, with particular reference to the development of Smart Schools, and to evaluate progress with respect to knowledge management in school education.Design/methodology/approachThe research is designed around questionnaires based on a knowledge management conceptual framework administered to random samples of 50 teachers in 25 Smart Schools and 25 Non‐Smart Schools so as to be able to make comparisons.FindingsThe finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…In line with the above, Sharifah & Kamarul (2011) found that teachers who were ready to implement teaching using the ICT approach have a strong relation between work and behavior. Awang et al (2011) stated that teachers do not have the time to hold discussion sessions to share ideas to improve their teaching methods. Therefore, it can be said that the implementation of knowledge management through ICT can enhance the knowledge and skills of teachers at any time, but it involves high costs such as the purchase of ICT equipment and provision of facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the above, Sharifah & Kamarul (2011) found that teachers who were ready to implement teaching using the ICT approach have a strong relation between work and behavior. Awang et al (2011) stated that teachers do not have the time to hold discussion sessions to share ideas to improve their teaching methods. Therefore, it can be said that the implementation of knowledge management through ICT can enhance the knowledge and skills of teachers at any time, but it involves high costs such as the purchase of ICT equipment and provision of facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, online training can enhance the knowledge and skills of teachers at any time. This is because teachers do not have the time to hold discussion sessions to share ideas to improve their teaching methods Awang et al (2011). Therefore, the highly skills in ICT definitely give the teacher satisfaction as they can overcome the problems.…”
Section: The Relationship Between Teachers Ict Efficiency and Their Smentioning
confidence: 99%
“…The findings showed that the teachers were able to filter and improvise the acquired knowledge before storing it. Another comprehensive study by Awang et al (2011) revealed an outstanding result of knowledge management activities in schools. Even though only five primary schools were chosen from central Malaysia, high mean scores for knowledge capturing, knowledge creation, knowledge sharing, knowledge application and knowledge storage showed an effective practice of knowledge management in those schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, Tippins (2003) also stated that academic staffs viewed knowledge as a source of distinction, and thus refused to share all types of knowledge and experiences. Contrary, some of the teachers were reluctant to receive new knowledge from others as they thought it will bring threat and burden (Awang et al , 2011). Therefore, these two groups of teachers contributed to the existence of knowledge hoarding culture in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Giavrimis et al (2011) investigated why teachers take part in information and communication technology (ICT) programs and discussed their objectives. Awang et al (2011) discussed knowledge management in Malaysian school education. Yang and Huang (2008) performed a study of high school English teachers' behavior, concerns and beliefs in integrating information technology into English instruction.…”
Section: Introductionmentioning
confidence: 99%